BUYRAKLARDA URAT TOSHLARI HOSIL BO‘LISHI VA DAVOLASH YO‘LLARI - Oʻrmonov Muhammadyusuf Islomjon oʻgʻli; Mamazulunov Nurmuhammad (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Uric acid kidney stones are crystals formed due to excessive accumulation of purines in the urine. They often cause pain, difficulty in urination, and sometimes remain asymptomatic. This article explores the causes, prevention strategies, and treatment options for uric acid stones in an engaging and clear manner. Maintaining a healthy lifestyle, proper diet, and medications can effectively manage this condition.